2004
DOI: 10.1086/383208
|View full text |Cite
|
Sign up to set email alerts
|

The Strange Case of 133P/Elst-Pizarro: A Comet among the Asteroids

Abstract: We present a new investigation of the comet-asteroid transition object 133P/(7968) Elst-Pizarro. We find mean optical colors (BÀV = 0.69 AE 0.02, VÀR = 0.42 AE 0.03, RÀI = 0.27 AE 0.03) and a phase-darkening coefficient ( = 0.044 AE 0.007 mag deg À1 ) that are comparable both to other comet nuclei and to C-type asteroids. As in 1996, when this object's comet-like activity was first noted, data from 2002 show a long, narrow dust trail in the projected orbit of the object. Observations over several months reveal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

29
363
7

Year Published

2005
2005
2020
2020

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 196 publications
(399 citation statements)
references
References 56 publications
29
363
7
Order By: Relevance
“…Ejection velocities for dust emission from many MBCs tend to be relatively low compared to ejection velocities for classical comets, yet they are often comparable to the escape velocities of the corresponding nuclei (cf. Hsieh et al 2004). This competition between size preferences may be a highly consequential effect, meaning that there may be an 'ideal' size or size range for detectable MBCs where they are large enough to produce observable amounts of gas or dust emission but small enough that ejected dust can actually escape into space to become observable in the first place.…”
Section: Predictions From Energy Balancementioning
confidence: 99%
“…Ejection velocities for dust emission from many MBCs tend to be relatively low compared to ejection velocities for classical comets, yet they are often comparable to the escape velocities of the corresponding nuclei (cf. Hsieh et al 2004). This competition between size preferences may be a highly consequential effect, meaning that there may be an 'ideal' size or size range for detectable MBCs where they are large enough to produce observable amounts of gas or dust emission but small enough that ejected dust can actually escape into space to become observable in the first place.…”
Section: Predictions From Energy Balancementioning
confidence: 99%
“…As a result, comets contain a large amount of volatile material. Hsieh et al (2004) states that observationally, comets have a gravitationally unbound atmosphere called a coma and an accompanying tail, while asteroids do not. This is usually the result of near-surface ice sublimation where the comet is turned on and off as it goes through perihelion and aphelion, closest approach to the sun and furthest approach from the sun.…”
Section: Small Bodiesmentioning
confidence: 99%
“…When it was initially studied in 1996, the tail was deemed the result of a chance impact, and thereby predicted to extinguish. However, this conclusion was disproved when the comet-like activity was observed again by Hsieh et al in 2004. Hsieh et al (2004 studied the asteroid for several months and observed changes in the structure and brightness of the dust tail.…”
Section: Active Asteroidsmentioning
confidence: 99%
“…However, observations of renewed activity in and 2007(Hsieh et al 2004Lowry & Fitzsimmons 2005) rendered that explanation highly implausible. While recurrent activity (with intervening periods of inactivity) is commonly observed for classical comets where sublimation drives activity, it would be highly improbable for impacts to occur on the same object on three separate occasions in just 11 years, each time at a similar location in the object's orbit, when impacts are not seen to occur at anywhere near that frequency or regularity on other main-belt asteroids.…”
Section: Are They Actually Icy?mentioning
confidence: 99%
“…All of the currently known MBCs were discovered with telescopes smaller than 2 m in size, except for 176P which was discovered by the 8 m Gemini North telescope. Main-belt asteroids with sufficient ice on their surfaces to drive cometary activity are unexpected, and so it has been hypothesized that MBCs may have instead preserved ice in subsurface layers over the age of the solar system, and that that ice has only recently become exposed, perhaps via excavation from an impact by another asteroid (Hsieh et al 2004;Capria et al 2012).…”
Section: Introductionmentioning
confidence: 99%